SHM_120786_HST_3D Ceramic Jug - Bonnevier, Helena; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a ceramic jug from the Middle Ages, collected in the field at Slottsfjärden in Kalmar and held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=665

Link to Sök I Samlingarna

https://samlingar.shm.se/object/17249601-1DB0-4AC4-A7E1-06697322F695
Keywords: 3D Model; Museum Object; Archaeology; Archaeology; Photogrammetry; History and archaeology; Archaeology/history; Dynamic Collections; Slottsfjärden; Swedish Middle Ages; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi